A Flat Process Calculus for Nested Membrane Interactions - C. Bodei; L. Brodo; R. Bruni; D. Chiarugi (Scientific Annals of Computer Science)
The link-calculus has been recently proposed as a process calculus for representing interactions that are open (i.e., that the number of processes may vary), and multiparty (i.e., that may involve more than two processes). Here, we apply the link-calculus for expressing, possibly hierarchical and non dyadic, biological interactions. In particular, we provide a natural encoding of Cardelli's Brane calculus, a compartment-based calculus, introduced to model the behaviour of nested membranes. Notably, the link-calculus is flat, but we can model membranes just as special processes taking part in the biological reaction. Moreover, we give evidence that the link-calculus allows one to directly model biological phenomena at the more appropriate level of abstraction.